Analysis Students’ Scientific Explanation Skills Using Explanation Driven Inquiry Learning on Acid-Base Topic - Oktavia Sulistina; Hesti Puspitasari; Dedek Sukarianingsih (Department of Chemistry Education, UIN Sunan Gunung Djati Bandung, 2021)
This study analyzes students' scientific explanation skills using explanation driven inquiry (EDI) learning on acid-base topics. The method used a quasi-experimental design with a posttest-only control group design. The research sample consisted of two groups that 30 students each in EDI (experimental group) and guided inquiry (GI) (control group). The research instrument was essay questions. The EDI learning model provides better results than the guided inquiry (GI) learning model for students' scientific explanation skills. The quality of the students' scientific explanation skills reached the highest level (level 4). EDI class students were more likely to achieve it than the GI class.